Implication of microplastic presence in sediment and blood clams Anadara granosa (Mollusca: Bivalvia) in the Musi Estuary, Indonesia - M. AKBAR RAHMAN; ROZIRWAN ROZIRWAN; WIKE EKA AYU PUTRI; GUSTI DIANSYAH; MELKI MELKI; ICA DELYA; REDHO YOGA NUGROHO (Society for Indonesian Biodiversity, 2025)
Abstract. Rahman MA, Rozirwan, Putri WEA, Diansyah G, Melki, Delya I, Nugroho RY. 2025. Implication of microplastic presence in sediment and blood clams Anadara granosa (Mollusca: Bivalvia) in the Musi Estuary, Indonesia. Biodiversitas 26: 1720-1733. Microplastic pollution poses a serious risk to estuarine ecosystems, affecting sediments and benthic species. Blood clams Anadara granosa represent a significant commercial seafood product in Indonesia, including those from the Musi Estuary. This study investigated the risks associated with microplastic contamination in sediments and A. granosa in the Musi Estuary, located in South Sumatra, Indonesia. Sediment samples were extracted using sodium chloride (NaCl, 1.2 g cm-3) and hydrogen peroxide (30% H2O2). In contrast, A. granosa samples were digested with 10% KOH for microplastic extraction. The abundance and shape of microplastics were analyzed from both samples. Pollution risk assessment was conducted through the calculation of the Pollution Load Index (PLI), Nemerow Pollution Index (NPI), and Bioconcentration Factor (BCF). The results revealed the presence of microplastics in sediments, with a mean abundance of 1.31±0.41 particles/g dw, while in A. granosa, it was 21.05±10.31 particles/ind. Both samples exhibited high microplastic bioaccumulation (NPI>2), although the pollution load remained relatively low (minor category, PLI<10). The bioconcentration factor between A. granosa and sediment was determined to be 23.28, indicating that the A. granosa absorbed microplastics present in the sediment. These findings highlight the significant bioaccumulation potential of microplastics in A. granosa within the Musi Estuary. The local community and government need to establish mitigations for future microplastic management efforts.